Public perception and willingness to undergo cosmetic procedures during the COVID-19 pandemic: A cross-sectional study - Ibrahim Alreshidi; Assil Albrekeit; Ruaa Alharithy (Wolters Kluwer Medknow Publications, 2022)
Background: As a result of the spread of coronavirus disease (COVID-19) at the beginning of 2020, many governments, including Saudi Arabia, have suspended operations in many agencies. Most of the dermatologists have restricted their practice, including cosmetic procedures, to ensure social distancing. On May 7, 2020, Saudi authorities have reduced the restriction of COVID-19 virus preventative measures, allowing clinics to start accepting patients with following the ministry of health protocols. Purpose: To evaluate the public's perception and willingness to undergo cosmetic procedures during the COVID-19 outbreaks in Saudi Arabia. Methods: A descriptive, cross-sectional, questionnaire-based study was carried out among the individuals who lack typical symptoms of COVID-19 infection in Saudi Arabia. A self-designed web-based questionnaire was developed; content face validity and a pilot study were done. The questionnaire was distributed electronically from May 8 to May 31, 2020. Results: A total of 656 individuals who lack typical symptoms of COVID-19 infection were included in this analysis. Only 10.5% of participants expressed their will to do cosmetic procedures during the COVID-19 pandemic. More than 90% of the participants believed that the COVID-19 pandemic was either somewhat serious (52.9%) or very serious (38.7%). The willingness to do cosmetic procedures during the COVID-19 pandemic remained unaltered when the price was discounted (P < 0.001), and when infection control measures were ensured (P < 0.001). Conclusion: The COVID-19 pandemic had a negative impact on the practice of cosmetic dermatology. Fear of transferring the infection to a beloved home member is the main reason to avoid these procedures. Generating well-structured safety guidelines to decrease the risk of this unusual virus transmission in dermatology practice and creating financial incentives may help increase the public willingness to do these cosmetic procedures during this pandemic.